Institutional Pathways to Africa’s Resource Self-Reliance: A Systematic Review of Governance, Digitalisation and Sustainability Dynamics - Okere, Wisdom; Ambe, Cosmas; Vilakazi, Sanele Phumlani (International Journal of Economics and Financial Issues, 2026)
Africa’s persistent paradox of resource abundance and economic dependence underscores a structural gap between abundant natural resources and institutional capabilities. This study synthesises multidisciplinary evidence on how governance quality and digitalisation jointly promote sustainable, self-reliant resource economies in Africa. Adopting the PRISMA methodology, we reviewed research outputs (2017-2025) and applied a tightened inclusion criterion requiring governance or digitalisation-related content in the titles, abstract and keywords. The study adopts an integrated framework that incorporates institutional theory, the Resource-Based View and Dynamic Capabilities Theory to explain how institutional factors and digital readiness co-develop resilience and inclusivity in value creation. From the search, twenty-one (21) studies met the criteria, concentrated in energy (12) and extractive sectors, with institutional analyses distributed across Micro (2), Meso (3) and Macro (16) levels. Findings reveal a sharp rise in scholarship between 2023 and 2025, reflecting increased attention to digital governance reforms and sustainability-driven policy frameworks aligned with IFRS S1/S2 and the Agenda 2063 framework. Thematically, findings reveal that: (i) governance transparency and enforcement are drivers of accountability, (ii) digitalisation is a catalyst for traceability, fiscal efficiency and stakeholder inclusivity, and (iii) sustainability is achieved through the integration of governance and digitalisation. The study proposes a triadic conceptual framework that links institutional capacity, digital transformation and sustainability, highlighting the need for unified regional standards, adaptive and flexible governance, and capacity-building across Africa. The study concluded with actionable pathways, including regulatory coherence, data transparency, cross-border digital infrastructure, green industrial policies, and public-private partnerships, all aimed at Africa’s energy and extractive sectors.